3D SEISMIC TOMOGRAPHY Vp, Vs, AND Vp/Vs RATIO BENEATH GEDE VOLCANO, WEST JAVA, INDONESIA - ARYANTI - NIM: 12313016 , ERISHA
Gede Volcano (West Java, Indonesia), is located 60 km southern of Jakarta with altitude of 2.598 m above the sea level. This stratovolcano is categorized into type A volcano (magmatic eruptions after 17th century) and within one of the regions with highest population density in the world. The characteristic eruptions occurred in Gede Volcano are commonly small and short in period. Almost every year, the seismicity of Gede Volcano significantly increased and was dominated with volcanotectonic A-type event, volcano-tectonic B-type event, tectonic event, and tremor. The last swarm occurred in February-March 2012, was caused by the tectonic movement of the fault and intrusion. The objective of this study is to find the low velocity zone due to the magmatic or weak zone. We picked manually the arrival time of P wave and S wave for the volcano tectonic events and local tectonic events of January 2016January 2017 period. Most of the hypocenters are having a fix depth solution, due to the azimuthal GAP > 180o. We also found a cluster between Gede Volcano and Pangrango Volcano at depth of 0 until 28,47 km under the mean sea level. Then the 1-D velocity model was updated and the hypocenters were relocated with VELEST33. The relocated hypocenters were getting near to the research area, and the hypocenter with fix depth solution became less. The updated velocity model, origin time, and hypocenter location were input to get the 3-D velocity model of P wave, S wave, and Vp/Vs ratio. Checkerboard test and derivative weight sum were done to set the inverse modelling parameters, but didn’t give a good resolution. The inversed model at depth -1, 0, 1 and 2 km below the mean sea level and the slice D-D’ were interpreted. From the velocity model, there were 3 velocity anomaly zones, consist of alterated rock zone, old magma conduit (future magma instrusions), and weak zone. The alterated rock zone was located at depth of -2 until -1 km, and was shown by the low Vp anomaly and high Vp/Vs anomaly. The old magma conduit zone was located at depth -2,5 until 2 km, and was shown with the high Vp anomaly and low Vp/Vs anomaly. And the weak zone (the fractured zone) was located at depth of 0 until 2 km below the mean sea level, and was shown with the low Vp anomaly and high Vp/Vs anomaly. The relocated hypocenters from SIMULPS12 were getting more near the research area (distributed at depth -1 until 20 km below the mean sea level).